Mathematical Analysis of Neural network - Theory and Computational Network - Kumar, J. Satish; B. Archana, B. Archana; Kumar, V. Senthil (Journal of Neonatal Surgery, 2025)
Neural networks revolutionized artificial intelligence and machine learning because their mathematical basis directly influences their operational efficiency and achievement of desired results. The research examines neural networks through theoretical calculation methods to study mathematical expressions and optimization techniques and stability assessment algorithms. Records of numerical training methods with their respective convergence properties appear in the analysis. Well-designed neural network structures require stringent mathematical models because they produce efficient and resistant network architectures.